Gastric Pneumatosis After Accidental Ingestion of Concentrated Hydrogen Peroxide: A Case Report - Christine X.Q. Pham (eScholarship Publishing, University of California, 2021)
Introduction: Hydrogen peroxide is a common oxidizing agent that if ingested may cause injury to the gastrointestinal tract or embolic events. Although therapy is primarily supportive, gastric perforation is a rare but serious complication of corrosive ingestion that may require surgical treatment. Case Report: We report the case of a 77-year-old male who presented for nausea and vomiting after accidentally ingesting approximately 150 milliliters of 35% hydrogen peroxide. Computed tomography revealed gastric pneumatosis and extensive portal venous air. The patient was admitted for observation with plans for endoscopy; however, due to the limitations of our small community hospital, he was transferred to a tertiary care center due to concern for a potential gastric perforation. Conclusion: The presence of portal venous air as a result of peroxide ingestion may be treated conservatively depending on presenting symptoms; however, severe injury such as gastrointestinal perforation may necessitate surgical intervention.